Design, synthesis, docking, and anticancer evaluations of new thiazolo[3,2-a] pyrimidines as topoisomerase II inhibitors - Mona S. El-Zoghbi; Samiha A. El-Sebaey; Hanan A. AL-Ghulikah; Eman A. Sobh (Taylor & Francis Group, 2023)
New thiazolopyrimidine derivatives 2, 3a-d, 4a-c, 5, 6a-c, and 7a,b were synthesised. All prepared compounds were evaluated by MTT cytotoxicity assay against three human tumour cell lines. Compounds 3c, 3d, 4c, 6a, 6b, and 7b exhibited potent to strong anticancer activity that was nearly comparable or superior to Doxorubicin. Compounds exhibiting significant cytotoxicity were further selected to study their inhibitory activity on the Topo II enzyme. Compound 4c was the most potent Topo II inhibitor with an IC50 value of 0.23 ± 0.01 µM, which was 1.4-fold and 3.6-fold higher than the IC50 values of Etoposide and Doxorubicin. Furthermore, compound 4c showed significant cell cycle disruption and apoptosis on A549 cells compared to control cells. Molecular docking of the most active compounds illustrated proper fitting to the Topo II active site, suggesting that our designed compounds are promising candidates for the development of effective anticancer agents acting through Topo II inhibition.